Restructuring and revamping of Agriculture Institute - Rana, Abdul Wajid; Haider, Zeeshan (International Food Policy Research Institute, 2021)
Agriculture, worldwide, has seen remarkable transformation in farming practices, institutional frameworks and policies during the last three decades. Dynamic international markets and the diffusion of bioinformatics technology are shifting farming towards a new organizational model. Production systems are seeking new forms of coordination and control, increasing demand for traceability of origin, and greater integration into international markets. Public research programs are looking beyond mono-cropping systems toward integration of farming, cattle-raising and forestry and whole agriculture innovation system. Global positioning systems (GPS) and computerized agricultural machinery linked via satellites is promoting precision agriculture where inputs are calibrated exactly to the differences in soil and farm activities while farmers are looking for their linkages with output markets for their produce. Commitments to international agreements and conventions regarding biodiversity, climate change, food security, and land use are creating a new bottom line for agricultural practices. This necessitates a new institutional and regulatory framework.